Trefoil factor 3 (TFF3) enhances the oncogenic characteristics of prostate carcinoma cells and reduces sensitivity to ionising radiation. Issue 1 (28th May 2015) - Perera, Omesha; Evans, Angharad; Pertziger, Mikhail; MacDonald, Christa; Chen, Helen; Liu, Dong-Xu; Lobie, Peter E.; Perry, Jo K.
Abstract Trefoil factor 3 (TFF3) is a secreted protein which functions in mucosal repair of the gastrointestinal tract. This is achieved through the combined stimulation of cell migration and prevention of apoptosis and anoikis, thus facilitating repair. Deregulated TFF3 expression at the gene and protein level is implicated in numerous cancers. In prostate cancer TFF3 has previously been reported as a potential biomarker, overexpressed in a subset of primary and metastatic cases. Here we investigated the effect of increased TFF3 expression on prostate cancer cell behaviour. Oncomine analysis demonstrated that TFF3 mRNA expression was upregulated in prostate cancer compared to normal tissue. Forced-expression models were established in the prostate cancer cell lines, DU145 and PC3, by stable transfection of an expression vector containing the TFF3 cDNA. Forced expression of TFF3 significantly increased total cell number and cell viability, cell proliferation and cell survival. In addition, TFF3 enhanced anchorage independent growth, 3-dimensional colony formation, wound healing and cell migration compared to control transfected cell lines. We also observed reduced sensitivity to ionising radiation in stably transfected cell lines. In dose response experiments, forced expression of TFF3 significantly enhanced the regrowth of PC3 cells following ionising radiation compared with control transfected cells. In addition, TFF3 enhanced clonogenic survival of DU145 and PC3 cells. These studies indicate that targeting TFF3 for the treatment of prostate cancer warrants further investigation.